Hackathons unboxed : a field guide to ideating, leading and winning - Chia, Alvin (Marshall Cavendish Business, 2018)
How much do you know about hackathons, besides the fact that they are highly intense sessions where teams of "hackers" compete to create a game-changing business solution? Whether a potential organiser, a future participant, or just wondering what else you need to break out of the conventional, this book is for you. Hackathons Unboxed takes you behind the scenes, to unpack the seeming magic that gives birth to groundbreaking ideas in just three short days. There are in fact a series of repeatable steps - a well-researched methodology that anybody can follow. But we don't just hack in a vacuum.